Analisis Swot: Strategi Pengembangan Hotel Syariah Bandar Lampung - Dewi, Tamara Synta; Kristanto, Herry; Astuti, Sri Yuli (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2025)
G Hotel Syariah is one of the 1-star hotels in Bandar Lampung. The hotel business is currently starting to revive after being inactive for the past 2 years due to Covid-19. Various strategies have been carried out by hotel management to increase visitors. However, competition from the emergence of new hotels is also a threat to their business which is suspected of experiencing a decline in business profits during the pandemic. G Hotel Syariah uses a Branding strategy in its management. This study aims to conduct the most appropriate analysis to develop G Hotel Syariah. The research method used is descriptive qualitative. By conducting interviews, documentation and questionnaires. The respondents in this study numbered 52. The analysis technique is SWOT analysis. The results obtained in the study were the IFAS value of 14.28 and the total EFAS value was 7.75, meaning that the best and most appropriate strategy to use is the S-O strategy or Strength and Opportunity. G Hotel Syariah must utilize its strengths and take advantage of opportunities to develop its hotel business.